Phages - An alternative to antibiotics? - International Livestock Research Institute (International Livestock Research Institute, 2021)
A short animation explaining why phages - viruses which infect bacteria - could be an effective alternative to antibiotics. Read about ILRI's research into phage therapy at: https://www.ilri.org/news/phages-viru... Animation created by ILRI / Annabel Slater.